2009
DOI: 10.1016/j.renene.2008.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between louvers and ceiling geometry for maximum daylighting performance

Abstract: a b s t r a c tThe impact of ceiling geometries on the performance of louvers was investigated using physical model experiments and Radiance simulations. Two performance indicators, the illuminance level and its distribution uniformity, were used to assess daylighting performance in a room located in a subtropical climate region. It was found that the performance of the louvers can be improved by changing the ceiling geometry. The illuminance level increased in the rear of the room, and decreased in the frontd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 18 publications
(25 reference statements)
0
31
0
Order By: Relevance
“…Therefore, physical scaled models were used to validate the results of the IES-Radiance simulation. Physical scaled model is able to replicate the behavior of light in a full-scale building [1,2,36,37] as previous research has also shown the performance and accuracy of the model in portraying daylight performance under actual sky conditions [31,32,38,39].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, physical scaled models were used to validate the results of the IES-Radiance simulation. Physical scaled model is able to replicate the behavior of light in a full-scale building [1,2,36,37] as previous research has also shown the performance and accuracy of the model in portraying daylight performance under actual sky conditions [31,32,38,39].…”
Section: Methodsmentioning
confidence: 99%
“…Variables affecting louvre daylight performance include width, distance between louvres, orientation and ceiling height. Freewan, Shao, and Riffat (2009) studied the effect of ceiling shape on louvers' performance in hot climate regions.…”
Section: Louvresmentioning
confidence: 99%
“…Overhangs are currently widely used, providing solar protection for glazed spaces and reducing loads during the cooling season. Some studies on the effect of louvres on a building's thermal performance and day-lighting performance (Freewan, Shao, & Riffat, 2009) have been carried out. Tzempelikos (2008) have given an overview of past and current approaches for computing the optical properties of shading devices.…”
Section: Introductionmentioning
confidence: 99%